The Relationship between Macronutrient Intake and Nutritional Status of the Elderly at Tresna Werdha Sabai Nan Aluih Sicincin Social Institution - Yhofa Nindra; Sri Nani Jelmila; Rosmaini Rosmaini (Science Midwifery, 2022)
The aging process results in physiological and psychological changes in old age thereby increasing the risk of nutritional problems. Macronutrient intake is one of the factors that affect nutritional status. This study aims to determine the relationship between macronutrient intake and the nutritional status of the elderly at Tresna Werdha Sabai Nan Aluih Sicincin Social Institution. This research is a correlative analytic research with cross sectional design. The sample of this research were 38 people. Data were analyzed using the Pearson correlation test. The results of this study showed that the average carbohydrate intake was 164.62 grams, the average protein intake was 35.44 grams and the average fat intake was 33.40 grams. As many as 55.3% of the elderly are at risk of malnutrition. The average body mass index is 21.28 kg/m2. There is a relationship between carbohydrate intake and body mass index (r=0.33, p=0.03) and there is no relationship between protein intake and body mass index (r=0.25, p=0.12) and there is no relationship between fat intake with body mass index (r=0.08, p=0.62). So that it can be concluded, the average intake of carbohydrates, protein and fat for the elderly at the Tresna Werdha Sabai Nan Aluih Sicincin Social Institution is less than the daily nutritional adequacy rate. There is a relationship between carbohydrate intake and body mass index and there is no relationship between protein and fat intake and body mass index.